Assessment of Alpha-Tocopheryl Acetate and Metformin Hydrochloride as Independent Agents on Human Dermal Fibroblast Viability: Findings from MTT Assay - Nayla Majeda Alfarafisa; Astrid Feinisa Khairani; Achadiyani Achadiyani; Yoan Chou; Fitri Aulia; Muhammad Bintang Firdaus (Althea Medical Journal, 2025)
Background: Alpha-tocopheryl acetate (Vitamin E) and metformin hydrochloride have been tested as anti-aging compounds at various concentrations. This study aimed to identify the most effective concentrations of alpha-tocopheryl acetate and metformin hydrochloride in promoting the viability of human dermal fibroblasts (HDFs), a primary cell type in skin aging research.